Hypolipidaemic and Cardioprotective Effects of Bee Bread Harvested from Stingless Bee (Heterotrigona Itama) in High-Fat Diet-Induced Obese Animal Model - Othman, Zaidatul; Wan Ghazali, Wan Syaheedah; Noordin, Liza; Mohd. Yusof, Nurul Aiman; Mohamed, Mahaneem (IIUM Medical Journal Malaysia, 2025)
INTRODUCTION: Bee bread has reached its research interest because of its high antioxidant and nutritional values. Our study aimed to characterize hypolipidaemic and cardioprotective effects of high-fat (F) diet-induced obese rats co-administered with bee bread. MATERIALS AND METHODS: Male Sprague-Dawley rats were randomly assigned as N group (rats fed with normal diet), F group (rats fed with F diet), FB group (rats fed with F diet and 0.5 g/kg/day bee bread), and FO group (rats fed with F diet and 10 mg/kg/day orlistat for 6 weeks). RESULTS: The FB group significantly had decreased levels of Lee obesity index, total fat pad, total cholesterol and low-density lipoprotein, and significantly had increased cardiac superoxide dismutase, glutathione peroxidase and catalase activities compared to the F group. Furthermore, the FB group demonstrated significant decreases in the levels of cardiac lipid peroxidation marker and fatty acid synthase activity with improvement in histological findings of heart and adipose tissues. CONCLUSION: These findings suggested that bee bread exerted hypolipidaemic and cardioprotective effects owing to its modulatory action on de novo synthesis of fatty acid.